THE ETHICAL AND LEGAL ASPECTS OF HEALTH POLICY ON ELECTRONIC MEDICAL RECORDS IN INDONESIA - Larasati, Ta; Fardiansyah, Ahmad Irzal; Saketi, Dwi; Nusa Dewiarti, Azelia (Universitas Lampung, 2024)
The government has addressed the development of electronic medical records (RME) through Minister of Health Regulation (Permenkes) No. 24 of 2022, ensuring their legality in healthcare facilities across Indonesia. The primary goal is to integrate all patient data, enabling the Ministry of Health to map the health status of Indonesian citizens, including information about various diseases. However, principles related to medical records, particularly confidentiality, must be observed to prevent violations and guarantee the privacy of patient data, reflecting healthcare professionals' ethical responsibilities. The use of electronic medical records raises concerns about potential data leaks, necessitating the establishment of security measures and identification of responsible parties in case of breaches. Research indicates that challenges remain in implementing RME across healthcare facilities, including limited internet access and the lack of preparedness among practitioners, clinics, health centers, and hospitals. Therefore, the Ministry of Health must undertake extensive outreach and training initiatives to address these issues and enhance internet connectivity throughout the country.